2016
DOI: 10.21423/jrs-v04n03p001
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Label Claims of Internet-Purchased Hemp Oil and Cannabis Products as Determined using IMS and LC-MS : A Marketplace Survey

Abstract: In this paper we describe the use of ion mobility spectrometry (IMS) and liquid chromatography – high resolution mass spectrometry (LC-HRMS) to screen for the presence of cannabinoids and other potential hazards in a set of products with hemp oil and/or cannabinoid label claims purchased via the internet. Preliminary screening was performed using IMS to examine the products for the presence of cannabinoids, illicit drugs or undeclared pharmaceuticals before analysis by LC-HRMS to quantitatively determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The RSDs of the CBD calibrators used to develop the calibration curves were less than 10%, and no analyte signal was observed in the unspiked chocolate and gummy matrices (example shown in Figure S6). Several studies (presented in Table ) have reported the successful quantification of cannabinoids in Cannabis -infused matrices such as oils/liquids, ,,,,, food products, ,,,,,, concentrates, capsules, ,, and vape products. , Ciolino et al reported the average percent (%) recovery of five cannabinoids in various spiked matrices, including edible oils, foods, topicals, oral OTC (over-the-counter) pharmaceuticals, beverages, and dairy foods . Included within the food product category were milk and dark chocolate bars (extracted with acetonitrile) and a hard candy (extracted with 83% aqueous acetonitrile) …”
Section: Resultsmentioning
confidence: 99%
“…The RSDs of the CBD calibrators used to develop the calibration curves were less than 10%, and no analyte signal was observed in the unspiked chocolate and gummy matrices (example shown in Figure S6). Several studies (presented in Table ) have reported the successful quantification of cannabinoids in Cannabis -infused matrices such as oils/liquids, ,,,,, food products, ,,,,,, concentrates, capsules, ,, and vape products. , Ciolino et al reported the average percent (%) recovery of five cannabinoids in various spiked matrices, including edible oils, foods, topicals, oral OTC (over-the-counter) pharmaceuticals, beverages, and dairy foods . Included within the food product category were milk and dark chocolate bars (extracted with acetonitrile) and a hard candy (extracted with 83% aqueous acetonitrile) …”
Section: Resultsmentioning
confidence: 99%